Efficacy of rechallenge transcatheter arterial chemoembolization after lenvatinib treatment for advanced hepatocellular carcinoma. Issue 11 (21st September 2022) - Uchida‐Kobayashi, Sawako; Kageyama, Ken; Takemura, Shigekazu; Matsumoto, Kazuhiro; Odagiri, Naoshi; Jogo, Atsushi; Kotani, Kohei; Kozuka, Ritsuzo; Motoyama, Hiroyuki; Kawamura, Etsushi; Hagihara, Atsushi; Yamamoto, Akira; et al.
Abstract: Background and Aim: We evaluated the efficacy of rechallenge transcatheter arterial chemoembolization (TACE) after lenvatinib (LEN) treatment in patients with previous TACE failure/refractoriness. Methods: We enrolled 63 consecutive patients with a history of TACE failure/refractoriness prior to LEN treatment as a first‐line systemic therapy. We reviewed the clinical backgrounds and courses of the patients. Results: In total, 25 patients underwent rechallenge TACE after LEN due to LEN‐refractoriness (17 cases) or intolerance (8 cases). A complete or partial response was obtained for 13 (65.0%) of the 20 patients whose therapeutic effects were determined. The survival rate of patients who underwent rechallenge TACE was significantly higher than that of patients who did not undergo rechallenge TACE (median survival time, not reached vs 403 days, P = 0.015). Rechallenge TACE significantly reduced the risk of death in univariate (hazard ratio [HR] 0.24, 95% confidence interval [CI] 0.08–0.69, P = 0.008) and multivariate analyses (HR 0.26, 95% CI 0.08–0.80, P = 0.019). If complete or partial response was obtained by rechallenge TACE, the median survival time of these patients was significantly longer than those of the progressive disease (PD) group ( P = 0.05), and the median survival time of the PD group after rechallenge TACE was not different from that of the group who did not undergo rechallenge TACE ( P = 0.36). We did not observe a decrease in the ALBI score after TACE. Conclusion: Rechallenge TACE after LEN is an effective treatment that may result in a favorable prognosis. Abstract : We enrolled 63 consecutive patients with a history of TACE failure/refractoriness prior to LEN treatment as a first‐line systemic therapy, and of whom 25 patients underwent rechallenge TACE after LEN due to LEN‐refractoriness or intolerance. The survival rate of patients who underwent rechallenge TACE was significantly higher than that of patients who did not undergo rechallenge TACE(a), especially in BCLC‐A and B (b).